Execution of the “House Arrest”: Issues in Practice - Brovet, Tamara (Zbornik Instituta za kriminološka i sociološka istraživanja, 2023)
Imposition of imprisonment served in the premises where the convicted individual resides (called “house arrest”) emerges as one of the most prevalent alternative criminal sanctions in the practice of domestic courts, especially following the recent amendments to the Criminal Code, significantly reducing the possibility of imposing conditional sentences. The specificity of this sanction lies in the execution of the imprisonment itself, as it does not represent a separate punishment but a distinct manner of executing an unconditional prison sentence. This execution does not take place in a prison facility but rather in the premises where the convicted person resides, typically more favourable for the convicted individual. However, “house arrest”, although a form of executing a prison sentence, differs significantly from “conventional imprisonment” and, due to its characteristics, constitutes a sui generis form of deprivation of liberty. Despite the numerous advantages of this specific method of executing a prison sentence, categorised as an alternative criminal sanction based on its characteristics, significant problems arise in practice when implementing “house arrest”, especially during the initiation of its execution. The legislator has not precisely regulated this process, often leading to the impossibility of commencing its execution. Additionally, it is essential to note the reduced ability to monitor the offender's rehabilitation during the execution of “house arrest” compared to conventional imprisonment. In the latter, the offender serves the prison sentence in penal conditions, precisely within a specialised institution for the execution of prison sentences. The aim of this paper is to highlight the identified problems during the execution of this external criminal sanction in the practice of courts and to provide possible solutions to the problems occurring during the implementation of “house arrest”.